EXTREMELY LOW FREQUENCY (ELF) MAGNETIC FIELD RADIATION ANALYSIS OF TEMPE MATERIAL MATURITY - Agustina, Metthahera Anggun Dwi; Tias, Eka Rini Wahyuning; A.N, Nadhiefa Nissa’ul; Yushardi, Yushardi; Anggraeni, Firdha Kusuma Ayu; Meilina, Ike Lusi (EduFisika: Jurnal Pendidikan Fisika, 2023)
Electromagnetic waves in physics are waves composed of a magnetic field and an electric field whose propagation does not require an intermediary medium. Magnetic fields with Extremely Low Frequency (ELF) frequencies have a frequency range of 0 to 300 Hz. Electromagnetic waves can propagate without needing a medium, so they are called electromagnetic radiation with various types of electromagnetic waves which are differentiated based on their frequency. Electric fields are easily blocked, so their intensity will decrease if they are blocked by objects. Meanwhile, magnetic fields have characteristics that are not easily blocked so they can penetrate almost all materials. The aim of this conducted research is to examine the influence of Extremely Low Frequency (ELF) magnetic field exposure on pH in the tempe fermentation process. This research uses a Completely Randomized Design (CRD) research design to examine the effect of several treatments with a number of replications for several experiments. The research findings indicate that exposure to Extremely Low Frequency (ELF) magnetic fields affects the pH in the tempe fermentation process, as depicted by the variations in the tables presented in the research results. Tempe is one of the fermented products that generally uses soybeans as the main raw material that has been fermented and has excellent nutritional content. Fermentation in making tempe occurs due to the activity of the mold Rhyzopus oligosporus which is able to produce phytase enzymes that function to hydrolyze phytic acid into inositol and phosphate.